Pancreatic Cancer Heterogeneity Can Be Explained Beyond the Genome - Juiz, Natalia Anahi; Iovanna, Juan; Dusetti, Nelson (Frontiers in Oncology, 2019)
Pancreatic ductal adenocarcinoma (PDAC) remains a major health problem because it induces almost systematic mortality. Carcinogenesis begins with genetic aberrations which trigger epigenetic modifications. While genetic mutations initiate tumorigenesis, they are unable to explain the vast heterogeneity observed among PDAC patients. Instead, epigenetic changes drive transcriptomic alterations that can regulate the malignant phenotype. The contribution of factors from the environment and tumor microenvironment defines different epigenetic landscapes that outline two clinical subtypes: basal, with the worst prognosis, and classical. The epigenetic nature of PDAC, as a reversible phenomenon, encouraged several studies to test epidrugs. However, these drugs lack specificity and although there are epigenetic patterns shared by all PDAC tumors, there are others that are specific to each subtype. Molecular characterization of the epigenetic mechanisms underlying PDAC heterogeneity could be an invaluable tool to predict personalized therapies, stratify patients and search for novel therapies with more specific phenotype-based targets. Novel therapeutic strategies using current anticancer compounds or existing drugs used in other pathologies, alone or in combination, could be used to kill tumor cells or convert aggressive tumors into a more benign phenotype.